O Custo do Ruído no Planeamento das Infraestruturas de Transporte Rodoviário/Noise Cost Evaluation on Road Planning - Cecília Rocha (2010)
The quality of life of the population living in urban areas, not only the Portuguese, as the European and even the world, has been demonstrating a growing degradation. There are multiple dimensions embodied in the definition of "quality of life", which means, "individuals' perceptions of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns", according to the definition issued by the World Health Organization (WHO), "a broad ranging concept affected in a complex way by the persons' physical health, psychological state, level of independence, social relationships and their relationship to salient features of their environment" (WHOQOL Group 1995).A variety of studies show an increasing proportion of the population living in cities, fact that associated with a continuing expansion of new transport infrastructure with the passage of a larger number of vehicles, mostly relating to road transport, has largely contributed to this deterioration.The theme of this thesis deals with the relationship between the characteristics of environmental noise, in particular of road noise, urban planning options to which different municipalities have committed to and the impact of those decisions (or lack of decision) in the quality of life of the population in general and the potential consequences of restraining the "acquired" construction rights of urban land owners.To accomplish the objectives of quantifying the negative interference of road traffic noise, were studied several themes correlated with environmental acoustics. Considered of particular importance and in addition to matters concerning environmental acoustics, were issues related to transport economy and territorial planning. The combination of these three thematic made possible the quantification of the road traffic noise cost in Portugal.In this thesis were applied concepts associated with transport economy, which have allowed the quantification of noise externalities, that is to say, economic valuation of noise damaging effects in the population in particular with regard to health problems and exposed person's annoyance. It was possible to conclude that noise externalities represent approximately 0.25 per cent of PIB2007, about 400 million Euros per annum ("central values" estimate).Also in the transport economy sphere of influence, there was an attempt to quantify the noise mitigation measures used to minimize noise at the source (pavement solutions with enhanced acoustic performance) and in the wave path (noise barriers) on the roads which are part of the principal road network. The analysis of investments, for which was possible to gather the required information, resulted in the computation of an expense close to 18 million Euros in noise barriers and almost to 12 million Euros of additional cost for enhanced pavements to which will be added, in a twenty years period, approximately 100 million Euros in pavement replacements.Regarding territorial planning, were used related theories for the quantification and valuation of potential real estate tax revenue losses arising from environmental noise levels higher than the limits listed in the third Portuguese Noise Code (RGR), for noise zoning assigned by municipalities. It was concluded that the potential loss of real estate tax revenue (IMI), for the overall Portuguese municipalities, might achieve 120 million Euros per year, approximately 17% of total yearly revenue of IMI.Keywords :Environment; environmental noise; territorial planning; transports economics; noise externalities; real estate taxation (IMI)